Magickal astrology eaudiobook Use the power of the planets to create an enchanted life. - Alexander, Skye (Tantor Media, 2019)
"Astrology and magick are links between universal forces and earthly experience." —Skye Alexander Magickal Astrology shows you how to use cosmic forces to enhance your personal growth and magickal work. In addition to providing a historic overview of astrology's impact on architecture, the body, music, and language, the book includes a thorough explanation of how to assess your birth chart and information on working with planetary cycles, transits, lunar energies, eclipses, and more. Chapters include: ● Magick and the Astrological Elements ● Working with the Elements in Rituals ● Your Magick Toolbox ● Working with Solar and Lunar Energies ● Planetary Powers ● Magickal Botanicals ● Crystals and Gemstones ● Timing Magick Work ● Predicting the Future with Astrology Here, veteran astrologer Skye Alexander offers numerous ideas and inspiration for incorporating star power in rituals, celebrations, and everyday life.